Implementasi Perbup Kediri Tentang Pengelolaan Keuangan Desa Melalui SISKEUDES di Desa Wanengpaten Kabupaten Kediri - Angger Grindo Hargoro (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2023)
This article or article aims to describe and analyze the implementation along with the driving and inhibiting factors of the Kediri Regent Regulation Number 47 of 2018 concerning village financial management through the SISKEUDES application in Wanengpaten Village, Gampengrejo District, Kediri Regency. The problem is focused on policy implementation. In order to approach this problem, Edward III's theoretical references are used which consist of communication, resources, disposition, and bureaucratic structure. The research method in this research is descriptive qualitative. The data were collected through interviews and observation. This study concludes that it shows that the implementation of this regulation has not been fully implemented optimally. This can be seen from the top down communication dimension, so that the communication tends to be force majeure. The quality of the resources handling this program is far from being good. The educational background of village officials still does not meet the specifications to implement this policy. It is different from the dispositional dimension, related to the attitude and motivation of policy actors, which can be said to be positive. Activity executors have high enthusiasm and are solid in the context of the success of the SISKEUDES policy. Meanwhile, in terms of bureaucratic structure, there is no flow or policy implementation guidelines made by the internal village office. Factors that are key determinants of the successful implementation of this policy are the existence of adequate supporting facilities, and the existence of intense cooperation. Meanwhile, the factors that have the potential to cause the implementation of this policy to fail are inadequate human resource barriers, software that always experiences errors, and a lack of technical guidance which results in the slow development of operational mastery of the village apparatus.